Effects of Standard Basal Salt Mixtures and 1-Phenyl-3-(1,2,3-thiadiazol-5-yl) Urea Pre-treatments on Shoot Regeneration from Mature Cotyledons of Sweet Cherry in vitro - Ali Canli, Fatih (Asian Journal of Chemistry, 2010)
The influences of different basal salt compositions (QL, WPM and B5) and 1-phenyl-3-(1,2,3-thiadiazol-5-yl) urea (thidiazuron, TDZ) pre-treatments on shoot regeneration from sweet cherry cotyledons were investigated. Basal salt composition was critical for obtaining higher regeneration efficiencies from stored cherry cotyledons. TDZ pre-treatments did not enhance shoot regeneration. The highest regeneration efficiencies were obtained with WPM, followed by QL medium. The regeneration ability significantly decreased if B5 basal salt composition was used. WPM significantly increased both regeneration frequencies and shoot number per regenerating explant. In addition, shoot primordia formation on WPM was observable 4 days earlier than B5 medium.